1964
DOI: 10.1002/srin.196402318
|View full text |Cite
|
Sign up to set email alerts
|

Das System MnO(–FeO)–MgO(–CaO) und seine Verteilungsgleichgewichte mit flüssigem Mangan und Eisen‐Mangan‐Legierungen

Abstract: Die Systeme MnO–MgO und MnO–CaO, Elektronen‐ und Röntgenbeugungsuntersuchungen, Schmelzpunkte der reinen Stoffe, experimentelle Bestimmung der Soliduslinien, Berechnung der Liquiduslinien; das System MnO–MgO–CaO. Sauerstofflöslichkeit von Mangan und Eisen‐Mangan‐Schmelzen unter MnO‐Schlacken verschiedener Zusammensetzung, Manganseite des Systems Mn–O, Aktivität des MnO in MgO‐haltigen MnO‐Schlacken; das System MnO–FeO–MgO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

1968
1968
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…The Gibbs free energy of the Mn-O pair exchange reaction, Dg MnO was determined to reproduce the Mn-O relation of the Mn-rich side in the Fe-Mn melt at 1873 K (1600°C) measured by Shevtsov et al [41] and its temperature dependence of the relation measured by Takahashi and Hino, [42] respectively. As a result, the calculated O solubility in pure Mn melt fitted reasonably well with Schenck et al's [35] data as shown by a solid line in Figure 3.…”
Section: Fe-mn-o Systemsupporting
confidence: 76%
See 1 more Smart Citation
“…The Gibbs free energy of the Mn-O pair exchange reaction, Dg MnO was determined to reproduce the Mn-O relation of the Mn-rich side in the Fe-Mn melt at 1873 K (1600°C) measured by Shevtsov et al [41] and its temperature dependence of the relation measured by Takahashi and Hino, [42] respectively. As a result, the calculated O solubility in pure Mn melt fitted reasonably well with Schenck et al's [35] data as shown by a solid line in Figure 3.…”
Section: Fe-mn-o Systemsupporting
confidence: 76%
“…However, the reported O solubility data are scattered significantly as shown in Figure 3. Shenck et al [35] measured the O solubility using an induction furnace under deoxidized Ar atmosphere. However, there were noticeable discrepancies because of the impurities in their samples (N: 127-620 ppm, Fe: 1100-2900 ppm, C: 190-742 ppm, and Si:~100ppm).…”
Section: Fe-mn-o Systemmentioning
confidence: 99%
“…In Ref. [5], the calculated solidus is in good agreement with the experimentally obtained solidus. Also, through EDS analysis, it could be seen a strong presence of iron in point 1 of the Figure 3, see Table 3.…”
Section: Resultssupporting
confidence: 75%
“…4 -liquidus curve 3) is appreciably higher than the calculated one from an ideal-solution model in Ref. [5] (Fig. 4 -liquidus curves 1 and 2).…”
Section: Resultsmentioning
confidence: 64%
“…[2] The solidus temperature at each compo-THE principal components of the slags used in silicomansition was determined from visual observation of the start ganese and high-carbon ferromanganese smelting processes of melting. [2] The solidus temperature at each compo-THE principal components of the slags used in silicomansition was determined from visual observation of the start ganese and high-carbon ferromanganese smelting processes of melting.…”
Section: Introductionmentioning
confidence: 99%